City of God Redux: Inequality, Migration, and Violent Crime in Brazil between 1980 and 2000 - Tiago Freire (European Regional Science Association (ERSA), 2015)
There is a long-held belief that inequality is a major determinant of violent crime, particularly homicides. Some previous studies suggest that these results hold in the short term only. This could result from measurement error in income inequality. This study addresses the issue of measurement error in inequality by using the relationship between migration and inequality. Using rainfall shocks and changes in transport costs as exogenous sources of out-migration from rural areas in Brazil between 1980 and 2000, the study shows how migration from rural areas affects income inequality in urban areas. It finds that not only is there a negative and statistically significant relationship between inequality and crime in Brazil, and that the effects are much larger than previously thought, but also that this relationship holds in the long term.
Keywords: J61; J15; K42; R10; 330; Crime; Inequality; Rural-Urban Migration; Brazil